Cell Lysis of Bacillus subtilis Caused by Intracellular Accumulation of Glucose-1-Phosphate - Prasad, Chandan (J Bacteriol, 1974)
Mutants deficient in both glucose-6-phosphate dehydrogenase and phosphoglucose isomerase lysed 4 to 5 h after growth in nutrient medium containing glucose, or after prolonged incubation if the medium contained galactose. The lysis could be prevented by the addition of any other rapidly metabolizable carbon source such as fructose, glucosamine, or glycerol. The glucose-induced lysis was also abolished by introduction of a third mutation lacking phospho-glucose mutase activity but not by a third mutation lacking uridine diphosphate-glucose pyrophosphorylase or teichoic acid glucosyl transferase activity. Galactose-induced lysis was prevented only if the additional mutation abolished the uridine diphosphate-glucose pyrophosphorylase activity. The results showed that lysis was caused by the intracellular accumulation of glucose-1-phosphate, which in turn inhibited at least one of the two enzymes that convert glucosamine-6-phosphate to N-acetyl glucosamine-6-phosphate.